Effects of unburned tobacco smoke on inflammatory and oxidative mediators in the rat prefrontal cortex - Vivarelli, Fabio; Morosini, Camilla; Rullo, Laura; Losapio, Loredana Maria; Lacorte, Antonio; Sangiorgi, Stefano; Ghini, Severino; Fagiolino, Ivan; Franchi, Paola; Lucarini, Marco; Candeletti, Sanzio; Canistro, Donatella; et al. (Frontiers in Pharmacology, 2024)
Although the Food and Drug Administration has authorized the marketing of “heat-not-burn” (HnB) electronic cigarettes as a modified risk tobacco product (MRTP), toxicological effects of HnB smoke exposure on the brain are still unexplored. Here, paramagnetic resonance of the prefrontal cortex (PFC) of HnB-exposed rats shows a dramatic increase in reactive radical species (RRS) yield coupled with an inflammatory response mediated by NF-κB-target genes including TNF-α, IL-1β, and IL-6 and the downregulation of peroxisome proliferator-activated receptor (PPAR) alpha and gamma expression. The PFC shows higher levels of 8-hydroxyguanosine, a marker of DNA oxidative damage, along with the activation of antioxidant machinery and DNA repair systems, including xeroderma pigmentosum group C (XPC) protein complex and 8-oxoguanine DNA glycosylase 1. HnB also induces the expression of drug-metabolizing enzymes such as CYP1A1, CYP2A6, CYP2B6, and CYP2E, particularly involved in the biotransformation of nicotine and several carcinogenic agents such as aldehydes and polycyclic aromatic hydrocarbons here recorded in the HnB stick smoke. Taken together, these effects, from disruption of redox homeostasis, inflammation, PPAR manipulation along with enhanced bioactivation of neurotoxicants, and upregulation of cMYC protooncogene to impairment of primary cellular defense mechanisms, suggest a possible increased risk of brain cancer. Although the HnB device reduces the emission of tobacco toxicants, our findings indicate that its consumption may carry a risk of potential adverse health effects, especially in non-smokers so far. Further studies are needed to fully understand the long-term effects of these devices.